Surgical Management of Patellar Luxation in a Dog - Saharan, Sandeep; Poonia, Anju; Kumar, Amit; Sachin; Tiwari, Deepak Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
In dogs, patellar luxation is a common orthopedic problem. The luxation can be lateral, medial, or bidirectional. Medial and lateral luxation is usually diagnosed in small breed and giant breed dogs, respectively (Bosio et al., 2017). Patellar luxation is the result of various anatomic abnormalities involving the entire hind limb. The absence of the physiological pressure on the articular cartilage of the trochlear groove due to chronically luxated patella during growth may prevent the development of an adequately deep and wide groove (trochlear hypoplasia) (Lavrijsen et al., 2014). The correction of the luxation can be accomplished through the use of both soft tissue and osseous surgical methods or a combination of more than one procedure (Harsen, 2006). Soft tissue procedures include lateral imbrications, antirotational sutures and medial desmotomy. These techniques can be performed on immature individuals to reduce aberrant forces on growing bones and on mature patients to support bony procedures (Di Dona et al., 2018). Bony procedures include Tibial tuberosity transposition, Corrective osteotomies and Deepening of the trochlear groove by abrasion trochleoplasty, trochlear chondroplasty, wedge and block recession trochleoplasty. The goal of the repair is to repose the tendon’s insertion between the patella and tibia in order to create a trochlear groove that is deep and wide enough to embed about 50% of the patella above the trochlear ridges (Talcott et al., 2000).